Familial prevalence of psoriasis in patients with multiple sclerosis – results from an Australian survey - Mangkorntongsakul, Varitsara; Fontes-Villalba, Ariadna; Kwong, Chun-Ting Justin; Charlton, Olivia; McGuire, Helen Marie; Montague, Turlough; Phan, Kevin; Venkatesha, Venkatesha; Herkes, Geoffrey; Smith, Saxon; Parratt, John (Frontiers in Neurology, 2025)
BackgroundThe familial association of psoriasis with multiple sclerosis (MS) has been observed in several international studies. Whether this link is applicable in an Australian setting has yet to be established. The aim of this study was to evaluate the prevalence of psoriasis in family members of an MS cohort in the Australian population.MethodsA survey study of adult MS patients was conducted between 2018 and 2021 at the MS clinic, Royal North Shore Hospital, Sydney, Australia.ResultsA total of 204 MS participants, with mean age of 48.8 years, were included in the study. Of these participants, 67 were male (32.8%) and 137 were female (67.2%). An increased rate of psoriasis was found among family members of MS patients: 35 (17.2%) MS patients had family history of psoriasis, and 11 patients reported a history of psoriasis themselves. Of the 35 MS patients with family history of psoriasis, female participants were found to be at a higher risk of psoriasis (34.6%, n = 9/26) as compared to their male counterparts (22.2%, n = 2/9).DiscussionThis study demonstrates a significantly increased risk of psoriasis among family members of MS patients, suggesting overlap in genetic risk between the two immune-mediated diseases. Further prospective research is warranted to determine the characteristics of association in MS individuals with psoriasis or/and family history of psoriasis.